Rapid Effects of Hearing Song on Catecholaminergic Activity in the Songbird Auditory Pathway - Matragrano, Lisa L.; Beaulieu, Michaël; Phillip, Jessica O.; Rae, Ali I.; Sanford, Sara E.; Sockman, Keith W.; Maney, Donna L. (PLOS ONE, 2012)
Catecholaminergic (CA) neurons innervate sensory areas and affect the processing of sensory signals. For example, in birds, CA fibers innervate the auditory pathway at each level, including the midbrain, thalamus, and forebrain. We have shown previously that in female European starlings, CA activity in the auditory forebrain can be enhanced by exposure to attractive male song for one week. It is not known, however, whether hearing song can initiate that activity more rapidly. Here, we exposed estrogen-primed, female white-throated sparrows to conspecific male song and looked for evidence of rapid synthesis of catecholamines in auditory areas. In one hemisphere of the brain, we used immunohistochemistry to detect the phosphorylation of tyrosine hydroxylase (TH), a rate-limiting enzyme in the CA synthetic pathway. We found that immunoreactivity for TH phosphorylated at serine 40 increased dramatically in the auditory forebrain, but not the auditory thalamus and midbrain, after 15 min of song exposure. In the other hemisphere, we used high pressure liquid chromatography to measure catecholamines and their metabolites. We found that two dopamine metabolites, dihydroxyphenylacetic acid and homovanillic acid, increased in the auditory forebrain but not the auditory midbrain after 30 min of exposure to conspecific song. Our results are consistent with the hypothesis that exposure to a behaviorally relevant auditory stimulus rapidly induces CA activity, which may play a role in auditory responses.